Charting the Bibliometrics Landscape of Character, Building and School Research: Trends and Future Directions in Scopus Database (1923-2023) - Fantofik, Didy; Maksum, Muh. Nur Rochim; Salim, Hakimuddin; Mustofa, Triono Ali; Apriantoro, Muhamad Subhi (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2023)
The primary goal of this research is to assess the effectiveness of character education programs in schools in fostering positive attitudes, values, and behaviors among students. Additionally, it seeks to determine the impact, whether positive or negative, of character education on students' academic achievements. The study aims to evaluate how the school environment, encompassing school culture and the role of teachers, influences the development of students' character by examining the progression and orientation of character, building, and school research documented in publications indexed by Scopus. Employing bibliometric analysis techniques, the study delves into publications listed in the Scopus character, building, and school database spanning from 1923 to 2023. Data analysis was conducted using Excel and R/R-Studio, while VOSviewer visually analyzed the co-occurrence of keywords and document citations. The investigation identified 244 publications aligning with the predefined function, subject, and criteria. The findings revealed an annual growth rate of 2.52%, reaching its peak in 2021 with 25 publications on character, building, and school. The United States emerged as the leading contributor to publications, specifically affiliated with The George Washington University, which produced three documents. Notably, Hung, C.Y., emerged as the most relevant author, having authored two publications on character, building, and school. It is essential to note that the bibliometric analysis was confined to Scopus data, and the inclusion of other national and international databases should have been considered in the study. This research provides a concise overview of the literature available to researchers focusing on character, building, and school, offering recommendations for future research endeavors.